The Pengaruh Independensi, Self-Efficacy, dan Tekanan Ketaatan terhadap Audit Judgement dengan Kompleksitas Tugas sebagai Variabel Moderasi - Fitriana, Jihan; Gurendrawati, Etty; Utaminingtyas, Tri Hesti (Fakultas Ekonomi dan Bisnis dan LPPM Universitas Negeri Jakarta, 2023)
The purpose of this study was to analyze the effect of independence, self-efficacy, and obedience pressure on audit judgement with task complexity as a moderating variable. This study uses primary data with a sample of auditors at the Main Auditorate of State Finance 1 (AKN 1) at the Supreme Audit Agency of the Republic of Indonesia (BPK RI). This study determines the sample using purposive sampling method. Hypothesis testing carried out in this study used multiple linear regression analysis methods and Moderated Regression Analysis (MRA) with the SPSS 25. Based on the results of the analysis, it can be concluded that independence, self-efficacy, and obedience pressure have a significant effect on audit judgement. The results also show that task complexity is not able to moderate the influence of independence, self-efficacy, and obedience pressure on audit judgement.